1998
DOI: 10.3727/036012998816356544
|View full text |Cite
|
Sign up to set email alerts
|

Use of Alternative Therapies by a Low Income Population

Abstract: Patients in a family health center clinic were surveyed about their use of alternative/complementary medicine. These were mostly low-income individuals on Medicaid. The aim was to estimate prevalence and patterns of use of medically unconventional therapies such as chiropractic, homeopathy, and acupuncture in this population. Nearly two hundred patients (N = 199) filled out questionnaires inquiring about medical conditions and illnesses, personal health habits (physical activity, tobacco smoking, alcohol intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 4 publications
1
8
0
1
Order By: Relevance
“…This situation suggests that the parents with a high level of education had increased self-confidence, were highly knowledgeable about CAM methods, and could access sources more easily. Similar results were obtained when other studies in the literature were examined (Bulbul et al, 2009;Krastins, Ristinen, Cimino, & Mamtan, 1998;Ventola, 2010).…”
Section: Factors Affecting Cam Usesupporting
confidence: 90%
See 1 more Smart Citation
“…This situation suggests that the parents with a high level of education had increased self-confidence, were highly knowledgeable about CAM methods, and could access sources more easily. Similar results were obtained when other studies in the literature were examined (Bulbul et al, 2009;Krastins, Ristinen, Cimino, & Mamtan, 1998;Ventola, 2010).…”
Section: Factors Affecting Cam Usesupporting
confidence: 90%
“…This result obtained from the study is similar to the results of other studies. In the studies evaluating the incidence of CAM use, it was found that the percentage of use was higher in individuals having a higher income level (Hartmann et al., ; Krastins et al., ; Lim et al., ; Provenzi, Saettini, Barello, & Borgatti, ; Revuelta‐Iniesta et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…2 In Buffalo, NY, the health care disparity may be even worse because of the fact that no chiropractic benefits exist for Medicaid patients. Alternative therapies, including chiropractic, are used less by lower income 3 and African American populations 4 than the general population.…”
mentioning
confidence: 99%
“…Seventy per cent of such subjects used CAM. Although the usage rate was lower than the average, another survey found that 29% of low-income patients used CAM (Krastins et al, 1998). A high interest in organic products was reported by consumers earning less than $30,000 per year (Howell, 2001).…”
Section: Demographic Variablesmentioning
confidence: 99%
“…In a number of surveys, poorer health in general (a higher level of morbidity), not necessarily the presence of specific conditions, was associated with an increased usage of CAM (Astin, 1998;Bausell, Lee, & Berman, 2001b;Krastins, Ristinen, Cimino, & Mamtani, 1998;Welsko et al, 2000).…”
Section: Specific Medical Conditionsmentioning
confidence: 99%